IMPLEMENTASI PERATURAN BUPATI NOMOR 33 TAHUN 2018 TENTANG PEDOMAN TATA NASKAH DINAS PEMERINTAH KABUPATEN HUMBANG HASUNDUTAN - MONALISA, VERONICA; HUTAHAEAN, MARLAN; SINAGA, BUDIMAN NPD (LP2MTBM MAKARIOZ, 2023)
Official correspondence is one of the means of written communication used in the activities of the college administration. This research was carried out because of the irregularity of the official. This study aims to assess the suitability of the correspondence Humbang Hasundutan Goverment in making official letters implemented at Humbang Hasundutan Goverment with the Peraturan Bupati Nomor 33 Tahun 2018 tentang Tata Naskah Dinas di Lingkungan Pemerintah Kabupaten Humbang Hasundutan and the factors that influence them. The work units that are the speakers in this study are Sekretariat Daerah Kabupaten Humbang Hasundutan. This research uses descriptive method and the way to obtain data is by interview, observation, and documentation. The results obtained state that the implementation of correspondence management that include the completeness of the letter section, format, numbering, and the authority of the signatory to the letter are carried out not in accordance with the rector's regulation. The fac tors that influence the implementation of the correspondence management are code standardization, socialization, employee competency, use of information systems, and habit.